Relationship between postactivation potentiation of knee extensor muscles, sprinting and vertical jumping performance in professional soccer players - Requena, B.; de Villarreal, E. S. -S.; Gapeyeva, H.; Ereline, J.; Garcia, I.; Pääsuke, M. (The Journal of Strength and Conditioning Research, 2011)
Little is known about the relationship between postactivation potentiation (PAP) in human muscles, assessed by enhancement of twitch torque after a conditioning maximal voluntary contraction (MVC), and performance in activities requiring power and speed. Moreover, no studies have assessed PAP in soccer players who train power and endurance simultaneously. The purpose of the present study was to examine the relationship between twitch PAP in knee extensor (KE) muscles, and sprinting and vertical jumping performance in soccer players. Fourteen professional male soccer players with mean (SD) age 20.0 (3.6) years, height 177.9 (6.9) cm and body mass 70.5 (5.7) kg) were tested for 15-m sprint time, vertical jump height in countermovement (CMJ) and squat (SJ) jumps. PAP in KE muscles was induced by a 10-s isometric MVC. Electrically evoked twitches of KE muscles were evoked before and after the conditioning MVC. Immediately after the conditioning MVC, twitch peak torque (PT) and maximal rates of torque development and relaxation were significantly potentiated. A significant negative correlation was found between 15-m sprint time and jump height in CMJ (r = -0.63) and SJ (r = -0.57). PAP of twitch PT correlated significantly positively with jump height in CMJ (r = 0.61) and SJ (r = 0.64), and negatively with 15-m sprint time (r = -0.59). In conclusion, twitch PAP in KE muscles was significantly correlated with performance in vertical jumping and sprinting in male professional soccer players, whereas the magnitude of PAP in soccer players was similar to that observed previously in power-trained athletes.